Feminism without borders decolonizing theory, practicing solidarity - Mohanty, Chandra Talpade (Duke University Press, 2003)
"Bringing together classic and new writings of the trailblazing feministtheorist Chandra Talpade Mohanty, Feminism Without Borders addresses someof the most pressing and complex issues facing contemporary feminism. Forgingvital links between daily life and collective action and between theory andpedagogy, Mohanty has been at the vanguard of Third World and internationalfeminist thought and activism for nearly two decades. This collection highlightsthe concerns running throughout her pioneering work: the politics of differenceand solidarity, decolonizing and democratizing feminist practice, the crossingof borders, and the relation of feminist knowledge and scholarship to organizingand social movements. Mohanty offers here a sustained critique of globalizationand urges a reorientation of transnational feminist practice towardsanticapitalist struggles. Her probing and provocative analyses of key conceptsin feminist though - "home", "sisterhood", "community"–Lead the way toward a feminism without borders, afeminism fully engaged with the realities of a transnational world."
Keywords: anticapitalisme; approches et analyses; cours; discours dominant; fem1000; féminisme décolonial; féminisme postcolonial; histoire et politique; premier cycle; privilèges; systèmes d'oppressions; thématiques; transnationalisme

Sous le regard de l'Occident : recherche féministe et discours colonial - Mohanty, Chandra Talpade (Sexe, race, classe pour une épistémologue de la domination, 2009)
L’analyse de la construction intellectuelle et politique des « féminismes du tiers-monde » implique nécessairement deux mouvements simultanés : d’une part, une critique interne des féminismes « occidentaux » hégémoniques et, d’autre part, la formulation de problématiques et de stratégies féministes autonomes et ancrées géographiquement, historiquement, culturellement. Le premier mouvement consiste à déconstruire et décomposer ; le second, à concevoir et construire.
Première publication: 1984
Keywords: approches et analyses; cours; discours dominant; droits des femmes*; fem1000; féminisme décolonial; féminisme postcolonial; histoire et politique; incontournable; premier cycle; privilèges; systèmes d'oppressions; thématiques